A Comprehensive Analysis of Spitzer 4.5 μm Phase Curves of Hot Jupiters - Lisa Dang; Taylor J. Bell; Ying (Zoe) Shu; Nicolas B. Cowan; Jacob L. Bean; Drake Deming; Eliza M.-R. Kempton; Megan Weiner Mansfield; Emily Rauscher; Vivien Parmentier; Alexandra Rochon; Kevin B. Stevenson; et al. (The Astronomical Journal)
Although exoplanetary science was not initially projected to be a substantial part of the Spitzer mission, its exoplanet observations set the stage for current and future surveys with JWST and Ariel. We present a comprehensive reduction and analysis of Spitzer’s 4.5 μ m phase curves of 29 hot Jupiters on low-eccentricity orbits. The analysis, performed with the Spitzer Phase Curve Analysis pipeline, confirms that BLISS mapping is the best detrending scheme of the three independent schemes we tested for most, but not all, observations. Visual inspection remains necessary to ensure consistency across detrending methods due to the diversity of phase-curve data and systematics. Regardless of the model selection scheme, whether using the lowest BIC or a uniform detrending approach, we observe the same trends, or lack thereof. We explore phase-curve trends as a function of irradiation temperature, orbital period, planetary radius, mass, and stellar effective temperature. We discuss the trends that are robustly detected and provide potential explanations for those that are not observed. While it is almost tautological that planets receiving greater instellation are hotter, we are still far from confirming dynamical theories of heat transport in hot Jupiter atmospheres due to the sample’s diversity. Even among planets with similar temperatures, other factors like rotation and metallicity vary significantly. Larger, curated sample sizes and higher-fidelity phase-curve measurements from JWST and Ariel are needed to firmly establish the parameters governing day–night heat transport on synchronously rotating planets.